Contribution of the FilmArray Respiratory Panel in the management of adult and pediatric patients attending the emergency room during 2015–2016 influenza epidemics: An interventional study. (June 2019) - Busson, L.; Bartiaux, M.; Brahim, S.; Konopnicki, D.; Dauby, N.; Gérard, M.; De Backer, P.; Van Vaerenbergh, K.; Mahadeb, B.; Mekkaoui, L.; De Foor, M.; Wautier, M.; et al.
Highlights: FilmArray RP results do not impact antimicrobial prescription in the emergency room. FilmArray RP results do not impact admission and length of stay. Admission rate of children with a positive influenza B result was lower. Rapid molecular results for influenza improve antiviral prescription. Training physicians and selecting population to test might increase the impact. Abstract: Aim: To evaluate the contribution of a multiplex PCR for respiratory viruses on antibiotic and antiviral prescription, ancillary test prescription, admission and length of stay of patients. Methods: Two hundred ninety-one adult and pediatric patients visiting the emergency department during the 2015–2016 influenza epidemic were prospectively included and immediately tested 24/7 using the FilmArray Respiratory Panel. The results were communicated to the practitioner in charge as soon as they became available. Clinical and biological data were gathered and analyzed. Findings: Results from the FilmArray Respiratory Panel do not appear to impact admission or antibiotic prescription, with the exception of a lower admission rate for children who tested positive for influenza B. Parameters that account for the clinical decisions evaluated are CRP level, white blood cell count, suspected or proven bacterial infection and, for adult patients only, signs of respiratory distress. Length of stay is also not significantly different between patients with a positive and a negative result. A rapid influenza test result permits a more appropriate prescription of oseltamivir.